Digital War Discourse on Reddit : Analysing the Dissemination & Effect of the Russo-Ukrainian War-related Content - Penttinen, Julia (My University, 2024)
The core of the research for this bachelor’s dissertation was to find what kind of communities have formed on the forum site Reddit, and how these communities handle the subject of the Russo-Ukrainian war. The research method employed is a qualitative analysis. Three subreddits were examined to gather materials from their comment sections for analysis. The subreddits had great variations in their sizes, i.e. the number of members, to provide different environments to examine. While this study is in the field of digital culture, it also relies on the field of psychology since understanding human behaviours is a vital part of receiving a proper understanding of how these online spaces work. In addition, reliable research papers and studies centering around online communities and especially ones that have formed around darker subject matter, were not readily available. The findings of the study are that these three online communities in Reddit, all contain extreme content depicting real human suffering, even though all of them explicitly state that such posts should not be glorified and should only be posted under a specific tag that will warn the users of the possibly distressing imagery. However, posts like them only tended to be made into entertainment and the suffering of the Russian soldiers was glorified which led to the active culture dehumanisation in all three subreddits, through edited videos and foul language.
Keywords: War, Online discourse, OODT, Content, Community, Dehumanisation